Coiled-Coil Domain-Containing 68 Downregulation Promotes Colorectal Cancer Cell Growth by Inhibiting ITCH-Mediated CDK4 Degradation - Wang, Cong; Li, Hongyan; Wu, Lei; Jiao, Xueli; Jin, Zihui; Zhu, Yujie; Fang, Ziling; Zhang, Xiaodong; Huang, Haishan; Zhao, Lingling (Frontiers in Oncology, 2021)
Coiled-coil domain-containing 68 (CCDC68) plays different roles in cancer and is predicted as a tumor suppressor in human colorectal cancer (CRC). However, the specific role of CCDC68 in CRC and the underlying mechanisms remain unknown. Here, we showed that CCDC68 expression was lower in CRC than that in corresponding normal tissues, and CCDC68 level was positively correlated with disease-free survival. Ectopic expression of CCDC68 decreased CRC cell proliferation in vitro and suppressed the growth of CRC xenograft tumors in vivo. CCDC68 caused G0/G1 cell cycle arrest, downregulated CDK4, and upregulated ITCH, the E3 ubiquitin ligase responsible for CDK4 protein degradation. This increased CDK4 degradation, which decreased CDK4 protein levels and inhibited CRC tumor growth. Collectively, the present results identify a novel CDK4 regulatory axis consisting of CCDC68 and ITCH, which suggest that CCDC68 is a promising target for the treatment of CRC.